The effect of strontium and silicon substituted hydroxyapatite electrochemical coatings on bone ingrowth and osseointegration of selective laser sintered porous metal implants. - Aadil Mumith; Vee San Cheong; Paul Fromme; Melanie J Coathup; Gordon W Blunn (PLoS ONE)
Additive manufactured, porous bone implants have the potential to improve osseointegration and reduce failure rates of orthopaedic devices. Substantially porous implants are increasingly used in a number of orthopaedic applications. HA plasma spraying-a line of sight process-cannot coat the inner surfaces of substantially porous structures, whereas electrochemical deposition of calcium phosphate can fully coat the inner surfaces of porous implants for improved bioactivity, but the osseous response of different types of hydroxyapatite (HA) coatings with ionic substitutions has not been evaluated for implants in the same in vivo model. In this study, laser sintered Ti6Al4V implants with pore sizes of Ø 700 μm and Ø 1500 μm were electrochemically coated with HA, silicon-substituted HA (SiHA), and strontium-substituted HA (SrHA), and implanted in ovine femoral condylar defects. Implants were retrieved after 6 weeks and histological and histomorphometric evaluation were compared to electrochemically coated implants with uncoated and HA plasma sprayed controls. The HA, SiHA and SrHA coatings had Ca:P, Ca:(P+Si) and (Ca+Sr):P ratios of 1.53, 1.14 and 1.32 respectively. Electrochemically coated implants significantly promoted bone attachment to the implant surfaces of the inner pores and displayed improved osseointegration compared to uncoated scaffolds for both pore sizes (p<0.001), whereas bone ingrowth was restricted to the surface for HA plasma coated or uncoated implants. Electrochemically coated HA implants achieved the highest osseointegration, followed by SrHA coated implants, and both coatings exhibited significantly more bone growth than plasma sprayed groups (p≤0.01 for all 4 cases). SiHA had significantly more osseointegration when compared against the uncoated control, but no significant difference compared with other coatings. There was no significant difference in ingrowth or osseointegration between pore sizes, and the bone-implant-contact was significantly higher in the electrochemical HA than in SiHA or SrHA. These results suggest that osseointegration is insensitive to pore size, whereas surface modification through the presence of an osteoconductive coating plays an important role in improving osseointegration, which may be critically important for extensively porous implants.